Numerical assessment of the influence of foundation pinning, deck resistance, and 3D site geometry on the response of bridge foundations to demands of liquefaction-induced lateral soil deformation. Issue 79 (December 2015) - McGann, Christopher R.; Arduino, Pedro
Abstract: The 2010 Maule earthquake in Chile caused extensive lateral spreading at the site of the Mataquito river bridge. The surface soil deformation patterns and relatively minor structural damage to the bridge observed at this site suggest that foundation pinning effects played a prominent role in the overall response of the bridge abutments to the lateral spreading. 3D finite element analysis of a Mataquito river bridge abutment is used to examine the role of foundation pinning, lateral bridge deck resistance, the deck expansion gap, and the 3D site geometry on the response of the abutment and approach embankment to a simulated lateral spreading event. A parameter study using a second set of 3D finite element models is conducted in order to further investigate the influence of 3D geometric site effects, such as the width of the embankment crest and thickness of the non-liquefiable crust, on the response of deep foundations to kinematic demands consistent with lateral spreading. Abstract : Highlights: 3D FEA are used to assess effects of lateral spreading at Mataquito bridge in Chile. 3D FEA consider abutment, grouped shaft foundation, embankment, and native soil. Foundations resist lateral soil deformation through pile pinning and deck resistance. Model results also suggest the importance of 3D site geometry on foundation demands. 3D FE parameter study used to assess geometric site effects on foundation response.